1991
DOI: 10.1095/biolreprod44.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Protein Modification by Phosphorylation during the Process of Nuclear Membrane Dissolution in Puromycin-Treated Mouse Oocytes1

Abstract: The present study was undertaken to elucidate the mechanism of nuclear membrane dissolution (NMD) in puromycin-treated mouse oocytes. Treatment of germinal vesicle breakdown (GVBD) oocytes with puromycin (50 micrograms/ml) induced chromosome decondensation with formation of a polar body; these are designated nuclear membrane (NM) oocytes. After withdrawal of puromycin, NM oocytes underwent NMD (approximately 70%) during a 12-h culture period. Either dibutyryl cyclic AMP (dbcAMP, 25-100 micrograms/ml) or isobut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When metaphase I oocytes are cultured in cycloheximide-supplemented media, nuclei are formed and the first polar body is extruded (Clarke and Masui, 1983;Kang et al, 1991;Szollosi et al, 1991). These findings suggest that the capacity to support cell cycle progression is probably present during the metaphase I stage and only falls at the transition to anaphase.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…When metaphase I oocytes are cultured in cycloheximide-supplemented media, nuclei are formed and the first polar body is extruded (Clarke and Masui, 1983;Kang et al, 1991;Szollosi et al, 1991). These findings suggest that the capacity to support cell cycle progression is probably present during the metaphase I stage and only falls at the transition to anaphase.…”
Section: Resultsmentioning
confidence: 93%
“…Mouse oocytes treated with protein synthesis inhibitors at the first metaphase extrude the first polar body and form nuclei (Clarke and Masui, 1983;Kang et al, 1991). As shown by Szollosi et al (1991), these oocytes do not, however, proceed to second metaphase.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A majority of the oocytes with multiple female pronuclei had no polar bodies or only one and this observation suggests that the high incidence of multiple female pronuclear formation in the oocytes exposed to an electrical pulse was due to unsuccessful exocytosis of polar bodies. It has been shown that treatment of mouse oocytes with protein synthesis inhibitors at metaphase I stage induces the release of the first polar body and nuclear formation (Clarke and Masui, 1983;Kang et al, 1991;Szollosi et al, 1991). However, a polypeptide profile from pig oocytes activated by a n electrical pulse was very similar to that from pig zygotes penetrated by sperm (Sun et al, 1992), and inhibition of protein synthesis of IVM pig oocytes did not affect sperm penetration or male and female pronuclear formation (Ding et al, 199213).…”
Section: Discussionmentioning
confidence: 99%